Integration practice of outstanding traditional Chinese culture and ethnic education from the perspective of cultural philosophy - Chen, Lei (Transformação, 2024)
This study delves into the integration of traditional Chinese culture into ethnic education in minority regions. Utilizing a cultural philosophy framework, it investigates how enhancing educational mechanisms and transforming educational philosophies can boost cultural preservation and raise educational quality. By incorporating traditional cultural values into school curricula and activities, the research highlights effective methods for promoting the development and preservation of minority cultures. Using a mixed-methods approach, this study conducted qualitative interviews with educators and stakeholders in ethnic education, supplemented by students’ and educators’ quantitative surveys in minority areas. The findings underscore the importance of culturally informed educational practices in enriching these regions’ both the cultural and educational landscapes. Resumo: Este estudo ilustra a integração da cultura tradicional chinesa na educação étnica, em regiões minoritárias. Utilizando um quadro de filosofia cultural, investiga como melhorar mecanismos educacionais e transformar filosofias educacionais podem impulsionar a preservação cultural e aumentar a qualidade educacional. Ao incorporar valores culturais tradicionais nos currículos e atividades escolares, a pesquisa destaca métodos efetivos para promover o desenvolvimento e preservação das culturas minoritárias. Usando uma abordagem de métodos mistos, este estudo realizou entrevistas qualitativas com educadores e partes interessadas na educação étnica, suplementadas por pesquisas quantitativas de alunos e educadores, em áreas minoritárias. Os achados sublinham a importância das práticas educativas culturalmente informadas, para enriquecer tanto as paisagens culturais como educacionais dessas regiões.